Efek Mediasi Keterikatan Karyawan pada Pengaruh Keadilan Distributif dan Prosedural Terhadap Keinginan Berpindah - Edalmen, Patricia Fiona Ngadiman (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to determine the effect of distributive justice and procedural justice on turnover intention with employee engagement as a mediating variable at PT. XYZ The sample used was 83 respondents with a sample selection method using saturated sampling techniques. The study was conducted quantitatively and used a questionnaire to collect data. The results of this study concluded that distributive justice and procedural justice had a positive effect on employee engagement. Distributive justice has a negative effect on turnover intention, but the effect of procedural justice on turnover intention is not significant. Employee engagement acts as a partial mediation in distributive justice relations to turnover intention and acts as a full mediator on the influence of procedural justice on turnover intention. The next finding is that employee engagement has a negative influence on the desire to.